Identifikasi Komponen Volatil Asap Cair Daun Tembakau (Nicotiana tabacum L.) Rajangan - Kuntjahjawati Kuntjahjawati; Purnama Darmadji (agriTECH, 2004)
Tobacco smoke contains both a particulat and gaseous phase. Many compounds associated with tobacco smoke are known to cause certain health risks i.e; nicotine, nitrosamine, PAH compound etc. An alternative methode to minimize health risks is to produce liquid smoke. In this study, liquid smoke is produced by pirolysis of tobacco leaf containing 7.08% cellulose, 21.955% hemicellulosa , 9.115 % lignin and nikotin 3.05%. The pirolysis was carried out in a reactor at 400"C during 2.5 hours followed by condensation through in cold water condenser. The average yield of liquid smoke was 30.74%, tar 9.64% , char 44.1% and uncondensed gaseous phase 15.52%. These liquid smoke contained various compound such as 6.7% carbonyls, 0.74 % fenolic, 0.917% nicotine and 2.70% tar. Liquid smoke was extracted exhaustively using dichioromethane as solvent. Qualitative analysis of the extract was performed by means of Gas Chromatography and Mass Spectroscopy (GC-MS). Result of GC-MS showed that liquid smokes comprise least 25 macrocomponents. From GC/MS spectra were identified as methyl pyrazine, acethylene, dimethylpyrazine, 2, 4-hexadienal, phenol, dimethyl-ethyl pyrazine, trimethyl-ethylpyrazine, ethyldimethylpyrazine, diethyl-methylpyrazine, cyclobutane, butanamide, nicotine. myosmine, nornikotin dan 3- methylene-nonane.